PENGARUH DIMENSI KEADILAN TERHADAP BUDAYA ORGANISASI PADA LEMBAGA KEUANGAN SYARIAH DI YOGYAKARTA - Zamroni Nugraha; Muhammad Zakiy (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2021)
The importance of organizational culture for employees to create a conducive work environment, so it needs to be considered by every manager in a company. In creating this environment, the role of a leader is needed to provide justice for every employee in the organization. This study aims to determine the effect of procedural justice, compensation distributive justice and interactional justice on organizational culture. This research was conducted at Islamic financial institutions in Yogyakarta. This research uses descriptive quantitative research using the Likert scale. The sample in this study amounted to 219 employees who work at Islamic financial institutions in Yogyakarta using saturated sample techniques. In this study, researchers used samples at Bank Muamalat, BPRS Madina, Takaful Keluarga Syariah Insurance, BMT Bina Ihsanul Fikri, BMT Tamzis and Sharia Pegadaian. Data analysis used in this research is IBM SPSS version 21 with data analysis method using multiple linear regression. The results showed that procedural justice, compensation distributive justice and interactional justice had a positive effect on organizational culture. For this reason, creating a good organizational culture requires justice for all employees.